Effect of Alternative Production and Management Environments on Layer Reproduction System Development - Klein, A.N.; Anderson , K.E.; Golden, J.B. (International Journal of Poultry Science, 2013)
Three different production environments were evaluated for their impact on laying hen reproduction by assessing the ovary and oviducts for the presence of physiological variations. The three environments included free-range (FR = 60), cage-free (CF = 55) and battery cage (BC = 50). The ovaries and oviducts from these hens were collected and weighed during necropsy, then stored in a freezer at -20°F for later analysis. The analysis included the oviduct length and the number of Post-Ovulatory Follicles (POFs), atretic follicles, hierarchical follicles (H = 12-40 mm), small yellow follicles (SY = 5-12 mm), large white follicles (LW = 2-5 mm), small white follicles (SW =